ANALISIS PELAKSANAAN KEBIJAKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMA BAKTI SETIA NANGA PINOH KABUPATEN MELAWI - Ason Ason; Asep Eka Nugraha; Septian Peterianus (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This study aims (1) Analyzing the implementation of online learning policies, (2) describes the problem of the implementation of online learning faced by teachers, aligna and parents (3) describing the teacher strategy in overcoming the problem of online learning (4) describing the use of digital facilities and media Teachers in Online Learning (5) Describe Persipan Teachers in Penencanan, Implementation Process, and Assessment / Evaluation in Online Learners. This research is located at Bhakti Loyal Nanga Pinoh High School using a qualitative research method of qualitative description approach, the data source from the principal, deputy curriculum, and subject teacher. Research instruments use, observation sheets, interview sheets and documentation. Data collection techniques through observation, interviews, documentation. Data processing steps include: data reduction, data classification, data display, data interpretation and conclusion withdrawal. The research findings show (1) the implementation of the learning policy of the Covid-19 pandemic period was carried out flexibly in two ways, namely in the network and outside the network. The implementation of learning in the network (online) uses the Google Classroom, Google Form and WhatsApp application. While luring learning is carried out with limited face-to-face and hourly. In limited face-to-face learning, the teacher explains the subject matter broadly and gives assignments to students to be done in their homes. (2) The problems faced by teachers, students and parents of students in online learning are constrained by technology, namely not all students have seriousness / gadgets and the internet. (3) The strategy carried out by the teacher is to carry out learning in two ways, namely online and luring in overcoming the problem of online learning (4) digital media used by teachers in online learning using computer programs and software such as digital videos, video games , web pages and websites, including social media; Data and databases, digital audio, such as MP3, MP4 and e-books, in addition, supporting factors in learning at the Covid-19 pandemic period are good school management, high quality teachers and disciplined students and school facilities and infrastructure adequate. (5) In carrying out teacher learning to plan online learning and luring. The plan for implementing online learning contains core competencies, competency standards and indicators of competency achievement, by referring to learning objectives and material descriptions, teachers make tasks and questions about learning evaluations to guide students in the independent learning process and measure their learning outcomes. Based on research findings, it can be concluded that the implementation of online learning policies during the Covid-19 pandemic period will be effective and supported by good school management.Keywords: Implementation of Policy, Online Learning, Pandemic Covid-19 Period